(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
First of all, the author accomplishes the exact limits for all order derivatives of the global weak solutions of the n-dimensional incompressible magnetohydrodynamics equations, the n-dimensional incompressible Navier-Stokes equations and the two-dimensional incompressible dissipative quasi-geostrophic equation. Secondly, by making use of the exact limits, he establishes the improved decay estimates with sharp rates for all order derivatives of the global weak solutions, for all sufficiently large t. The author proves these results by making use of existing ideas, existing results and several new, novel ideas.